If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+3(-x)+2=2x+(-x)+13
We move all terms to the left:
5x+3(-x)+2-(2x+(-x)+13)=0
We add all the numbers together, and all the variables
5x+3(-1x)-(2x+(-1x)+13)+2=0
We multiply parentheses
5x-3x-(2x+(-1x)+13)+2=0
We calculate terms in parentheses: -(2x+(-1x)+13), so:We add all the numbers together, and all the variables
2x+(-1x)+13
We get rid of parentheses
2x-1x+13
We add all the numbers together, and all the variables
x+13
Back to the equation:
-(x+13)
2x-(x+13)+2=0
We get rid of parentheses
2x-x-13+2=0
We add all the numbers together, and all the variables
x-11=0
We move all terms containing x to the left, all other terms to the right
x=11
| 2^x+1=17^x | | x=x+(2x-17)+90+59 | | 2(2(x))+10+2(x)-x=2(x)+14 | | 1,3c=4,5 | | 1-5x=0.62-3.1x | | 2(2(-x))+10+2(-x)-(-x)=2(-x)+14 | | (18z+3)+32=23 | | 2(2(-x)+10+2(-x)-(-x)=2(-x)+14 | | 3.t=12 | | 11g-7=-5g-7 | | 6y+3y=117 | | 13x−42=21x+4 | | 3(-x)-(-5)+x=2x+13 | | -11.364-4.4n=1-1.59n | | n×6=30 | | (4r-8)-3=-36 | | 3×t=12 | | 1/5x-4/5=2/3x+1 | | 12x-3-4x=-11 | | 4(6x-5)=-5x+96 | | -38=7x+5x+10 | | m+1.7=-0.77-0.9m | | m+1.7=-0.77-0.9 | | m+1.7=-0.77-0.8 | | D=6t+32 | | 6r~1+6r=11 | | 27+2x+2x=180 | | x=-5x2+2x-1 | | X+3x(-4)=(-20) | | x+x/2=3000 | | D=4.2t+32 | | -103=-5x-6x+7 |